Pengaruh cendawan endofit terhadap biologi dan statistik demografi wereng batang cokelat Nilaparvata lugens Stál (Hemiptera: Delphacidae) - Amanda Mawan; Damayanti Buchori; Hermanu Triwidodo (Perhimpunan Entomologi Indonesia, 2015)
Endophytic fungi is an endosymbiont that lives within host plant tissues and does not necessary cause any harm to plants. This type of fungus are important as mediators in plant-herbivore interactions. One of the endophytic fungi in rice is Nigrospora sp. The effects of Nigrospora sp. on the biology and demographic statistic of Nilaparvata lugens Stál (Hemiptera: Delphacidae) were studied in the laboratory. We used Nigrospora sp. culture powder was used to inoculate the fungi to rice seeds by mixing 10 g of flour endophytic per 1 kg rice seeds. The mixture was then stored in damp and dark storage. Results showed that the rice seeds treated with endophytic fungi showed some resistance to N. lugens. Eggs and early stages of nymph mortality was increased, higher than the control. Endophytic fungi also affect the nymphs growth rates by slowing it down, prolonging N. lugens life cycle, preoviposition period as well as delayed the age at first reproduction. N. lugens population growth is effected by Nigrospora sp. in laboratory scale. Thus, it has the potential as an alternative way to control N. lugens population. In addition, inoculation of endophytic fungi could be a useful method for protecting rice plants from N. lugens.